Une idéologie incarnée. Les marques identitaires et le discours marketing les sous-tendant - Coutant, Alexandre (HERMES - Journal of Language and Communication in Business, 2010)
Marketers as advertising executives have long been concerned by brand equity. Nevertheless, classical economic theory used to undervalue its importance in the marketplace, as brand could hardly ﬁt the positivist epistemology it was relying on. Recent research arguing for a more comprehensive approach of consumption gave a new credibility to brands. Thus, the value of some of their intangible dimensions have been admitted enough to justify new kinds of communication strategies which are relying on brands’ identity strength. These socalled “identity brands” are supposed to operate as models for consumers. This paper is dealing with the theoretical justiﬁcation of this strategy and the assumed reasons why consumers should have a taste for these kinds of brands.